Correlation between microarray DNA hybridization efficiency and the position of short capture probe on the target nucleic acid. (July 2005) - Peytavi, Régis; Tang, Liu-ying; Raymond, Frédéric R.; Boissinot, Karel; Bissonnette, Luc; Boissinot, Maurice; Picard, François J.; Huletsky, Ann; Ouellette, Marc; Bergeron, Michel G.
The hybridization behavior of small oligonucleotides arrayed on glass slides is currently unpredictable. In order to examine the hybridization efficiency of capture probes along target nucleic acid, 20-mer oligonucleotide probes were designed to hybridize at different distances from the 5′ end of two overlapping 402- and 432-bp ermB products amplified from the target DNA. These probes were immobilized via their 5′ end onto glass slides and hybridized with the two labeled products. Evaluation of the hybridization signal for each probe revealed an inverse correlation with the length of the 5′ overhanging end of the captured strand and the hybridization signal intensity. Further experiments demonstrated that this phenomenon is dependent on the reassociation kinetics of the free overhanging tail of the captured DNA strand with its complementary strand. This study delineates key predictable parameters that govern the hybridization efficiency of short capture probes arrayed on glass slides. This should be most useful for designing arrays for detection of PCR products and nucleotide polymorphisms.